Feeding Ecology and Establishment of the Naturally-Colonized Freshwater Cichlid, Sarotherodon galilaeus (Pisces: Actinopterigii: Perciformes) from a Man-Made Lake, South-Benin, West Africa - GBAGUIDI, Houehanou MAG; ADITE, ALPHONSE (My University, 2016)
The freshwater cichlid, Sarotherodon galilaeus (Linné, 1758) is an economically and commercially important fisheries species that has naturally colonized and dominated a sand-dragged man-made freshwater lake of Ahozon (South-Benin) where the species made about 85.21% of the fish community. We investigated the feeding ecology of S. galilaeus in order to evaluate resource exploitation and the establishment of this species in Lake Ahozon. During wet, flood and dry seasons, 1189 individuals of S. galilaeus have been monthly sampled in the open water and in the aquatic vegetation habitats. The study showed that S. galilaeus consumed about seventy (70) food items dominated by algae (52.88%) composed of 28 families and 52 genera from blue-green a
Keywords: Algae; Artificial Lake; Diet Breadth; Diet Similarities; Ecomorphology; Establishment; Fisheries; Foraging Grounds; Tilapine Species